Treatment of diseases associated with cicatricial alopecia - Rudnicka, Lidia; Kaczorowska, Agnieszka; Waśkiel-Burnat, Anna; Rakowska, Adriana; Olszewska, Małgorzata (Dermatology Review/Przegląd Dermatologiczny, 2022)
Cicatricial (scarring) alopecia may result from perifollicular inflammation that destroys hair follicles and replaces them with connective tissue (primary cicatricial alopecia) or from damage done to follicles by other pathology that is not primarily directed against follicles (secondary cicatricial alopecia). Examples of such pathologies are: cutaneous tuberculosis, favus, morphea en coup de sabre. Hair follicle atrophy with clinical, trichoscopic and histological features of follicular drop out can also occur in the very late stage of non-cicatricial alopecia (e.g. androgenetic alopecia, alopecia areata). The fourth group of diseases with a similar clinical and sometimes also similar trichoscopic presentation, but of significantly different histology, is alopecia associated with neoplastic diseases (alopecia neoplastica). In this article, basic information about therapeutic methods that can be applied in selected diseases associated with cicatricial alopecia, with particular emphasis on primary cicatricial alopecia, has been summarized.